(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Health starts from the mouth. Having good oral health has an influence on overall general health, confidence levels and well being of a person. General health and oral health should hence not be seen as separate and they should be given equal importance. Our everyday habits such as cleansing habits, eating habits, etc, determine our oral hygiene status. Oral hygiene is not just an individual goal but a community goal on the whole. The aim of our study is to determine the oral health related knowledge, attitude and perception of young adults.Materials and Methods: A well structured questionnaire comprising 16 questions along with demographic data was circulated through google forms among 100 randomly selected young adults within Chennai. The responses were collected and analysed statistically using Chi square test on SPSS version 23.Results and Discussion: Oral health related knowledge and attitude was found to be very good. Majority of the participants gave equal importance to oral and general health and considered oral health to have an influence on general health. Females were found to have an overall better behaviour towards oral hygiene practices. P values were found to be less than 0.05 which indicates statistical significance. Conclusion: Hence, the oral health related knowledge, attitude and practice of young adults in chennai was assessed and it was found to be very good.